Spirulina platensis and silicon-enriched spirulina equally improve glucose tolerance and decrease the enzymatic activity of hepatic NADPH oxidase in obesogenic diet-fed rats. Issue 12 (15th November 2018) - Vidé, Joris; Bonafos, Béatrice; Fouret, Gilles; Benlebna, Melha; Poupon, Joël; Jover, Bernard; Casas, François; Jouy, Nicolas; Feillet-Coudray, Christine; Gaillet, Sylvie; Coudray, Charles
Abstract : The prevalence of metabolic syndrome components, such as obesity, glucose intolerance and hepatic steatosis, is rapidly increasing and becoming a major issue of public health. Abstract : The prevalence of metabolic syndrome components, such as obesity, glucose intolerance and hepatic steatosis, is rapidly increasing and becoming a major issue of public health. The present work was designed to determine the effects of Spirulina platensis (Sp) algae and silicon-enriched Sp on major metabolic syndrome components in obesogenic diet-fed rats. Forty male Wistar rats were divided into 4 groups. Ten rats were fed a control diet and 30 rats were fed a high fat (HF) diet. The HF groups were divided into three groups and supplemented with placebo or Sp or Si-enriched Sp for 12 weeks. Dietary intake and body weight were recorded. Oral glucose tolerance test and surrogate metabolic syndrome (insulin, leptin, adiponectin and lipids), mitochondrial function (enzymatic activity of respiratory chain complexes and β-hydroxyacyl-CoA dehydrogenase), NADPH oxidase activity and several long-established oxidative stress markers were measured in the blood and liver. The HF diet induced obesity, glucose intolerance, hepatic steatosis and huge metabolic alterations, associated with higher NADPH oxidase activity and lower hepatic sulfhydryl group and glutathione contents. Otherwise, the Sp and Sp + Si supplements showed some interesting effects on rat characteristics and particularly on blood and hepatic metabolic parameters. Indeed, the intake of Sp or Sp + Si mainly improved glucose tolerance and decreased the enzymatic activity of hepatic NADPH oxidase. Overall, Si supplementation of spirulina does not appear to have more beneficial effects than spirulina alone. Other experiments with different species of rats/mice, different diets or different durations of diet intake should be undertaken to confirm or invalidate these results.